ANALISIS YURIDIS PENJATUHAN PUTUSAN OLEH HAKIM TERHADAP PELAKU PEMALSUAN E-KTP PEMILIHAN UMUM - Kana, Nelci Duru; Leo, Rudepel Petrus; Manafe, Deddy R Ch (Petitum Law Journal, 2025)
This study examines the verdict in Case No. 105/Pid. Sus/2023/PN Kupang, in which Yan Quarius Bunga, a legislative candidate, was found guilty of falsifying an E-KTP to meet election requirements based on Article 520 of Law No. 7/2017 Concering on Elections and Article 55(1) of the Criminal Code. The judges highlighted the defendant's intent (dolus) and his position as a medeplegen (participant) in a structured scheme involving political elites, but imposed a light of 1 month probation and a small amount of fine, taking into account mitigating factors such as the defendant's cooperation and document revision. Critically, this verdict contradicts the maximum sanction stipulated by law, which is 6 years in prison, which has the potential to reduce the deterrent effect on election crimes. This study highlights the weaknesses of the system: (1) inadequate sanctions for organized crimes involving political actors, (2) failure to hold intellectual perpetrators (party officials) accountable, and (3) procedural errors, such as the return of the laptop used for falsification. Normative and empirical methods show tensions between retributive and restorative justice, with the verdict favoring rehabilitation over democratic integrity. The case reflects the paradoxical role of the judiciary in combating electoral fraud, highlighting the importance of coherent law enforcement to maintain public trust in democracy. Systemic legislative reforms to prevent identity fraud and strengthen electoral transparency are recommended, so that the democratic process does not become a mere administrative formality vulnerable to manipulation.